Effect of Short, Animated Video Storytelling on Maternal Knowledge and Satisfaction in the Perinatal Period in South Africa: Randomized Controlled Trial - Maya Adam; Zwannda Kwinda; Mithilesh Dronavalli; Elizabeth Leonard; Vān Kính Nguyễn; Vusani Tshivhase; Till Bärnighausen; Yogan Pillay (JMIR Publications, 2023)
BackgroundInnovative mobile health (mHealth) interventions can improve maternal knowledge, thereby supporting national efforts to reduce preventable maternal and child mortality in South Africa. Studies have documented a potential role for mobile video content to support perinatal health messaging, enhance maternal satisfaction, and overcome literacy barriers. Short, animated storytelling (SAS) is an innovative, emerging approach to mHealth messaging. ObjectiveWe aimed to measure the effect of SAS videos on maternal knowledge and user satisfaction for mothers enrolled in antenatal care programs at 2 public health facilities in the Tshwane District of South Africa. MethodsWe used a randomized controlled trial with a nested evaluation of user satisfaction. Participants were randomized 1:1 into Standard-of-Care (SOC) Control, and SAS Intervention groups. The intervention videos were delivered through WhatsApp, and 1 month later, participants responded to telephone surveys assessing their knowledge. The intervention group then participated in a nested evaluation of user satisfaction. ResultsWe surveyed 204 participants. Of them, 49.5% (101/204) were aged between 25 and 34 years. Almost all participants self-identified as Black, with the majority (190/204, 93.2%) having completed secondary school. The mean overall knowledge score was 21.92/28. We observed a slight increase of 0.28 (95% uncertainty interval [UI] -0.58 to 1.16) in the overall knowledge score in the intervention arm. We found that those with secondary education or above scored higher than those with only primary education by 2.24 (95% UI 0.76-4.01). Participants aged 35 years or older also scored higher than the youngest age group (18-24 years) by 1.83 (95% CI 0.39-3.33). Finally, the nested user satisfaction evaluation revealed high maternal satisfaction (4.71/5) with the SAS video series. ConclusionsWhile the SAS videos resulted in high user satisfaction, measured knowledge gains were small within a participant population that was already receiving perinatal health messages through antenatal clinics. The higher knowledge scores observed in older participants with higher education levels suggest that boosting maternal knowledge in younger mothers with lower education levels should continue to be a public health priority in South Africa. Given the high maternal satisfaction among the SAS video-users in this study, policy makers should consider integrating similar approaches into existing, broad-reaching perinatal health programs, such as MomConnect, to boost satisfaction and potentially enhance maternal engagement. While previous studies have shown the promise of animated video health education, most of this research has been conducted in high-income countries. More research in underresourced settings is urgently needed, especially as access to mobile technology increases in the Global South. Future studies should explore the effect of SAS videos on maternal knowledge in hard-to-reach populations with limited access to antenatal care, although real-world logistical challenges persist when implementing studies in underresourced South African populations. Trial RegistrationPan African Clinical Trials Registry PACTR202203673222680; https://tinyurl.com/362cpuny